2012
DOI: 10.1007/s00253-012-4432-2
|View full text |Cite
|
Sign up to set email alerts
|

Malic enzyme activity is not the only bottleneck for lipid accumulation in the oleaginous fungus Mucor circinelloides

Abstract: Commercial interest in microbial lipids is increasing due to their potential use as feedstock for biodiesel production. The supply of NADPH generated by malic enzyme (ME; NADP+-dependent; EC 1.1.1.40) has been postulated as being the rate-limiting step for fatty acid biosynthesis in oleaginous fungi, based mainly on data from the zygomycete Mucor circinelloides studies. This fungus contains five genes that code for six different ME isoforms. One of these genes, malA, codes for the isoforms III and IV, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
103
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 38 publications
7
103
1
Order By: Relevance
“…Recently, leucine metabolism was found to be another bottleneck in lipid accumulation in the oleaginous fungus M. circinelloides (37). In that work, the overexpression of the LEU2 gene (a gene encoding ␤-isopropylmalate dehydrogenase, involved in leucine biosynthesis) significantly increased the lipid content, in accordance with previous observations in Saccharomyces cerevisiae (74).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recently, leucine metabolism was found to be another bottleneck in lipid accumulation in the oleaginous fungus M. circinelloides (37). In that work, the overexpression of the LEU2 gene (a gene encoding ␤-isopropylmalate dehydrogenase, involved in leucine biosynthesis) significantly increased the lipid content, in accordance with previous observations in Saccharomyces cerevisiae (74).…”
Section: Discussionsupporting
confidence: 80%
“…However, the molecular mechanism of efficient lipid biosynthesis is still not well understood in oleaginous fungi in general and in M. alpina in particular. PAH and its cofactor BH 4 have been suggested to be essential for lipid metabolism in higher organisms (31)(32)(33)(34)(35)(36), and some amino acid metabolism pathways have been postulated to be involved in fatty acid biosynthesis in oleaginous fungi (37,38). However, the functional significance of the phenylalanine-hydroxylating system in the biosynthesis of lipids and closely related compounds has yet to be fully elucidated.…”
mentioning
confidence: 99%
“…It has been reported that Leu metabolism is involved in the generation of the acetyl-CoA required for fatty acid biosynthesis in the oleaginous fungus Mucor circinelloides (Vorapreeda et al, 2012;Rodríguez-Frómeta et al, 2013). In addition, catabolism of amino acids such as Ala and Gln could provide carbon skeletons directed to fatty acid elongation (Schwender et al, 2006;Junker et al, 2007;Hockin et al, 2012).…”
Section: Bcca Catabolism Affects Tag Biosynthesismentioning
confidence: 99%
“…Malic enzyme (ME; EC 1.1.1.40) was considered the sole NADPH provider for fatty acid synthesis in oleaginous microbes (3). Some evidence, however, indicated that ME is only one of several NADPH sources (4,5). We and others have recently demonstrated that the pentose phosphate pathway (PPP), specifically the glucose-6-phosphate dehydrogenase (G6PD; EC 1.1.1.49) and the 6-phosphogluconate dehydrogenase (PGD; EC 1.1.1.44) genes, plays a major role during microbial fatty acid synthesis (1,2,6).…”
mentioning
confidence: 99%